The role of sleep in the relation between young children's mobile media use and effortful control - Nathanson, Amy I.; Beyens, Ine (British journal of developmental psychology, 2018)
We explored the relations among young children's mobile media use, sleep, and a form of self‐regulation, temperamental effortful control (EC), among a national sample of 402 mothers who completed an online survey. We found that the relation between mobile media use and EC was moderated by children's sleep time. Tablet use was negatively related to EC only among children who slept less at night (40% of our sample). However, hand‐held game player use was positively related to EC among children who slept longer at night (60% of our sample). In addition, sleep quality was a mediator in the relation between evening tablet use and EC. Evening use related to later bedtimes, more bedtime resistance, and worse sleep duration, and these indicators of poor sleep quality, in turn, predicted weaker EC. Statement of contribution What is already known on this subject? Young children are spending increasing amounts of time with mobile media, such as tablets and hand‐held game players. Media exposure is related to children's self‐regulation. Media exposure is related to children's sleep quality. What does this study adds? Number of sleep hours moderates the relation between mobile media use and EC among young children. Tablet time is negatively related to EC among young children who get fewer sleep hours. Hand‐held game playing is positively related to EC among young children who get greater sleep hours. Sleep quality mediates the relation between evening tablet time and EC among young children.